DEVELOPMENT OF INTERACTIVE ACCOUNTING DIAGNOSTIC TEST MODEL BASED ON ICT - Listiadi, Dr. Agung (International Journal of Scientific Research and Management (IJSRM), 2022)
Learning is an activity that is inseparable from human life. By learning humans are able to develop the potentials that they carry from birth so that later they are able to adapt themselves to meet their needs. With learning expected changes in behavior in accordance with the expected goals. But sometimes behavioral changes that are expected do not occur even if they are not in accordance with the expected goals, so that learning difficulties are born. To help solve the problem of learning difficulties including doing diagnostic tests. Diagnostic tests are used to determine students' difficulties in mastering certain competencies. As technology develops, interactive ICT-based diagnostic tests are absolutely necessary to be a solution in diagnosing learning difficulties. This research produces a product in the form of ICT-based interactive diagnostic tests. This ICT-based diagnostic test in addition to being interactive is also able to generate passing grades, set scores automatically, randomize questions automatically, and arrange variations of questions automatically. As for developing this diagnostic test model using Thiagarajan development research design that is the 4D development model consisting of the defining (Define), Designing, Developing, and Disseminate stages. Diagnostic evaluation is one of the evaluation functions that requires procedures and competencies higher than the educator role as an evaluator. Diagnostic evaluation is an evaluation that has a special emphasis on healing student learning difficulties that are not solved by the improvement formula that is usually offered in the form of evaluation formative. Diagnostic evaluation can also be interpreted as an evaluation that is used to determine student weaknesses so that based on these weaknesses can be given appropriate treatment.